(untitled) (Global Journal of Human-Social Science, 2014)
This paper contains certain considerations on the High-Speed Railway HSR Station s area and its surroundings as well as the reasons and effects thereof The complexity and wide range of possible scenarios require a more specific context pertaining to medium-sized cities and a specific location of the station in those cities i e the city centre From the analysis based on the fieldwork carried out in certain stations in Germany as well as from the study of their accessibility level German cases are compared to other examples in Europe especially to examples in a country in which HSR was implemented at the same time Spain It can be concluded that there are material differences on the ways to approach the revitalisation of stations and the urban surroundings thereof in order to take advantage of the building s renovation project and the reorganisation of the railway environment as an important engine of urban renovation